Social Influences and Job Satisfaction among Teachers - Astorias- Espanola, Marjorie (JPAIR Institutional Research, 2013)
Education is a process of transferring knowledge to the learners. This transfer of knowledge takes place in the classroom. The teachers are human resources in the academe who deal with different personalities inside the classroom. Aside from doing usual tasks in school, they are also considered as the key implementers of educational trends. The investigation aimed to provide information on the extent of job satisfaction among the teachers of the extramural studies centers of Palawan State University. A descriptive research method was utilized to gather information related to the job satisfaction of the teachers. This method describes the characteristics of people or the community. Results of the study showed that the respondents are satisfied in their work environment in terms of preparation factors, physical working condition, faculty salary, security of tenure, benefits and privileges but undecided in the case "faculty development opportunity". They are satisfied in the written and verbal feedback. In the social influences, the respondents rated "very satisfied" in relationship with peers, supervisor and students. Test of association shows the significant relationship in status and benefits and privileges, a highest degree earned and salary and security of tenure, faculty development opportunity, tenure and written/verbal feedback. This study concluded that social influences is given more weight than work situation in determining job satisfaction, and some form is associated with job satisfaction of the teachers.
Keywords: Education; Teachers; Job satisfaction; descriptive-survey; Philippines